PMO-130 Altered acetyl-coa metabolism in hepatic mitochondrial impairment in in vitro models of hepatic cellular steatosis. (28th May 2012) - Lockman, K; Burgess, K E; Lee, P; Pryde, A; Hayes, P C; Filippi, C; Plevris, J N
Abstract : Introduction: Increased ketogenesis, in the presence of unaltered β-oxidation, is a feature of human steatohepatitis. This is thought to be attributable to decreased acetyl-coA entry to tricarboxylic acid cycle with mitochondrial impairment. In this study, we examined the diversion of acetyl-coA towards free fatty acid (FFA) biosynthesis and mevalonate pathways (including vitamin D3, steroids hormones and bile acids) in the presence of mitochondrial dysfunction and triglyceride accumulation. Methods: Human hepatoblastoma C3A cells were treated with; oleate or various combinations of octanoate (O), lactate (L), pyruvate (P) and ammonia (N) for 72 h. Metabolites that correspond to the intermediates of FFA biosynthesis, mevalonate pathways were measured using metabolomics study. Results: We have previously shown that LPON treatment, but not oleate, affected mitochondrial function as evidenced by decreased respiration and ROS formation with concomitant enhanced ketogenesis despite the similarities in triglyceride accumulation. Using metabolomics analysis, we identified three metabolites that correspond to FFA biosynthesis, three were bile acids and three were the derivatives of steroid hormones and vitamin D3 synthesis. We also identified mevalonate and 7-dehydrodemosterol, the intermediates of cholesterol biosynthesis. The concentrations of FFA biosynthesis intermediates were higher with LPON compared with oleate (3-oxo-tetradecanoate (p=0.005) and 3-oxo-hexadecanoate (p=0.02)). Although mevalonate (p=0.37) and 7-dehydrodesmosterol (p=0.46) levels were higher with oleate than that seen with LPON, these differences did not reach statistical significance. In contrast, bile acids were significantly elevated with oleate than LPON ((taurocholate (p=0.002), glycocholate (p=0.001), (6RS)-22-oxo-23, 24, 25, 26, 27-pentanorvitamin D3 6, 19-sulphur dioxide adduct (p=0.04) and 1, 25-dihydroxy-2, 4-dinor-1, 3-secovitamin D3 (p=0.0006). Conclusion: These data suggest that, aside from enhanced ketogenesis, impaired mitochondrial function is also associated with acetyl-coA diversion towards FFA synthesis, but not mevalonate pathways. These differences are likely to reflect cellular demand in the presence of decreased ATP formation with mitochondrial dysfunction. Competing interests: None declared.